Safety and Efficacy of Combined Yttrium 90 Resin Radioembolization with Aflibercept and FOLFIRI in a Patient with Metastatic Colorectal Cancer - Andre De Souza; Kevin Pelham Daly; James Yoo; Muhammad Wasif Saif (Case Reports in Oncological Medicine)
Background. When associated with isolated four or fewer liver foci, metastatic colorectal cancer is amenable to surgical resection. Alternative therapeutic methods for isolated liver metastases include radioembolization with yttrium 90 (Y90) and transarterial chemoembolization (TACE). We present here a case of a patient with two sites of liver metastatic disease from colorectal cancer who underwent Y90 radioembolization combined with aflibercept and FOLFIRI. Case Report. A 56-year-old female with history of bilateral breast cancer and metastatic colon cancer with prior hemicolectomy and 4 previous chemotherapy regimens developed liver metastasis. She was started on aflibercept and FOLFIRI and concurrently underwent two treatments of radioembolization with Y90, initially targeting the largest right lobe tumor, and then a subsequent treatment targeting the smaller left lobe tumor with retreatment of the right lobe tumor. Her liver metastases exhibited partial response on imaging utilizing the modified RECIST criteria. Interestingly, the patient CEA levels decreased after the procedure. Discussion. This is the first reported case of a patient managed with radioembolization with Y90 combined with aflibercept, an anti-VEGF treatment, and FOLFIRI. An ongoing randomized clinical trial aims to define the role of combined targeted therapy and chemotherapy with radioembolization with Y90.